How to talk about Hybridity? Culture-theoretical modelings of a well-known concept (KULT_online, 2015)
In analysis of the ‘hybridity hype’ that has occurred in the humanities during the last two decades, Ottmar Ette and Uwe Wirth focus in their conference volume Nach der Hybridität. Zukünfte der Kulturtheorie on the limits of the concept of hybridity. Based on 13 interdisciplinary articles, the authors open up new experimental spaces that allow for modelling or even overcoming the concept of hybridity. Along these lines, this miscellany provides new research angles on intercultural, intermedial as well as intertextual relationships that scrutinise simplistic bipolarities and re-essentializations.